Educational and health outcomes of schoolchildren in local authority care in Scotland: A retrospective record linkage study - Michael Fleming (Public Library of Science (PLoS), 2021)
Background Looked after children are defined as children who are in the care of their local authority. Previous studies have reported that looked after children have poorer mental and physical health, increased behavioural problems, and increased self-harm and mortality compared to peers. They also experience poorer educational outcomes, yet population-wide research into the latter is lacking, particularly in the United Kingdom. Education and health share a bidirectional relationship; therefore, it is important to dually investigate both outcomes. Our study aimed to compare educational and health outcomes for looked after children with peers, adjusting for sociodemographic, maternity, and comorbidity confounders. Methods and findings Linkage of 9 Scotland-wide databases, covering dispensed prescriptions, hospital admissions, maternity records, death certificates, annual pupil census, examinations, school absences/exclusions, unemployment, and looked after children provided retrospective data on 715,111 children attending Scottish schools between 2009 and 2012 (13,898 [1.9%] looked after). Compared to peers, 13,898 (1.9%) looked after children were more likely to be absent (adjusted incidence rate ratio [AIRR] 1.27, 95% confidence interval [CI] 1.24 to 1.30) and excluded (AIRR 4.09, 95% CI 3.86 to 4.33) from school, have special educational need (SEN; adjusted odds ratio [AOR] 3.48, 95% CI 3.35 to 3.62) and neurodevelopmental multimorbidity (AOR 2.45, 95% CI 2.34 to 2.57), achieve the lowest level of academic attainment (AOR 5.92, 95% CI 5.17 to 6.78), and be unemployed after leaving school (AOR 2.12, 95% CI 1.96 to 2.29). They were more likely to require treatment for epilepsy (AOR 1.50, 95% CI 1.27 to 1.78), attention deficit hyperactivity disorder (ADHD; AOR 3.01, 95% CI 2.76 to 3.27), and depression (AOR 1.90, 95% CI 1.62 to 2.22), be hospitalised overall (adjusted hazard ratio [AHR] 1.23, 95% CI 1.19 to 1.28) for injury (AHR 1.80, 95% CI 1.69 to 1.91) and self-harm (AHR 5.19, 95% CI 4.66 to 5.78), and die prematurely (AHR 3.21, 95% CI 2.16 to 4.77). Compared to children looked after at home, children looked after away from home had less absenteeism (AIRR 0.35, 95% CI 0.33 to 0.36), less exclusion (AIRR 0.63, 95% CI 0.56 to 0.71), less unemployment (AOR 0.53, 95% CI 0.46 to 0.62), and better attainment (AIRR 0.31, 95% CI 0.23 to 0.40). Therefore, among those in care, being cared for away from home appeared to be a protective factor resulting in better educational outcomes. The main limitations of this study were lack of data on local authority care preschool or before 2009, total time spent in care, and age of first contact with social care. Conclusions Looked after children had poorer health and educational outcomes than peers independent of increased neurodevelopmental conditions and SEN. Further work is required to understand whether poorer outcomes relate to reasons for entering care, including maltreatment and adverse childhood events, neurodevelopmental vulnerabilities, or characteristics of the care system. In this record-linkage study in Scotland, Michael Fleming and colleagues compare educational and health outcomes for children who are in the care of their local authority with the outcomes of their peers. Author summary Why was this study done? Looked after children, defined as children placed in the care of their local authority, comprise a vulnerable cohort exhibiting poorer educational and health outcomes compared to peers. Only a few small sample studies have been conducted in the UK, and a recent systematic review reported an urgent need for more population-wide research into the educational outcomes of children placed in social care services. To our knowledge, no previous UK studies have dually investigated educational and health outcomes of looked after children compared to peers using an unselected, nationwide cohort. What did the researchers do and find? We linked together 9 Scotland-wide databases to compare educational and health outcomes of looked after children against peers, adjusting for sociodemographic, maternity, and comorbidity confounders. Looked after children had increased risk of school absenteeism and exclusion; special educational need (SEN); poor academic attainment; unemployment; hospitalisation and mortality; and treatment for epilepsy, attention deficit hyperactivity disorder (ADHD), depression, and neurodevelopmental multimorbidity. Among children in care, those looked after away from home had less absenteeism, less exclusion, less unemployment, and better attainment. What do these findings mean? Looked after children had poorer health and educational outcomes than peers independent of increased neurodevelopmental conditions and SEN. Among those in care, being cared for away from home appeared to be a protective factor resulting in better educational outcomes. Further work is required to understand whether poorer outcomes relate to reasons for entering care, including maltreatment and adverse childhood events, neurodevelopmental vulnerabilities, or characteristics of the care system.